First evaluation of a traditional Portuguese alcoholic beverage, prepared with maceration of juniper berries - Anjos,Ofélia (2013)
The alcoholic drink called aguardente de zimbro is a traditional Portuguese alcoholic beverage made by the people living around Serra da Estrela, using the maceration of juniper berries in different distillates like arbutus spirit, marc spirit and wine spirit. Traditionally homemade for own consumption in rural families, this beverage is now sold to tourists and promoted and included in the food patrimony of the region. However, there is a lack of technical and scientific information about this beverage. A first evaluation of this beverage is done in this work, based on its sensory and physicochemical characteristics. A few commercial samples, two homemade and another two samples of alcoholic beverages made with juniper were analysed in this work. Several analytical determinations, namely density, alcoholic strength, dry matter, total acidity, fixed acidity, volatile acidity, the pH, chromatic characteristics, methanol, acetaldehyde, ethyl acetate, fusel alcohols and total antioxidant activity were done on the samples with the aim of characterising these Portuguese flavoured juniper spirits. The descriptive sensory analysis of these drinks was also done in order to find the more characteristic sensory attributes of the drink. The results show that under the label aguardente de zimbro there are several drinks, with a yellow colour, but with several differences in physicochemical composition and sensory description. In fact, these drinks, with ethanol content from 37.7 to 48.3 % vol. present values of acidity from 25 to 1360 mg/L, pH from 3.91 to 5.89, dry matter 0.75 to 75.24 g/L and density from 0.9446 to 0.9770 g/cm³. Important differences were also observed in the chromatic characteristics, volatile composition and total antioxidant activity. Therefore, further research must be done in order to characterise this traditional drink.